2018
DOI: 10.3390/ijms19020589
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral B-Cell Subset Distribution in Primary Antiphospholipid Syndrome

Abstract: Background: B-cell differentiation and B-cell tolerance checkpoints may be different in antiphospholipid syndrome (APS) from systemic lupus erythematosus (SLE) and can help to understand differences between them. Our aim was to define alterations of B-cell subsets in patients with primary APS (pAPS) and to compare them with SLE patients and healthy controls (HC). Methods: Cross-sectional study including three study groups: 37 patients with pAPS, 11 SLE patients, and 21 age- and gender-matched HC. We determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…APS and SLE share some clinical features, such as multiorgan manifestations, and the aPL profile and complement activation. At the same time, there are differences in the serum autoantibodies detected in both syndromes and we have recently demonstrated that the B cell phenotype differs between pAPS and SLE ( 8 ). From a pathogenic point of view, both entities are inflammatory disorders in which the activation of the innate immune response triggers an exacerbated acquired immune response ( 9 ).…”
Section: Introductionmentioning
confidence: 92%
“…APS and SLE share some clinical features, such as multiorgan manifestations, and the aPL profile and complement activation. At the same time, there are differences in the serum autoantibodies detected in both syndromes and we have recently demonstrated that the B cell phenotype differs between pAPS and SLE ( 8 ). From a pathogenic point of view, both entities are inflammatory disorders in which the activation of the innate immune response triggers an exacerbated acquired immune response ( 9 ).…”
Section: Introductionmentioning
confidence: 92%
“…Abnormal B cell maturation and differentiation is the underlying cause of this autoantibody production, and numerous studies have triggered a great deal of interest in the possibility of a crucial role for activated B cells and B cell subsets in the pathophysiology of autoimmune diseases, including rheumatoid arthritis (RA), Sjögren's syndrome (SS), multiple sclerosis (MS) and systemic lupus erythematosus (SLE) [5][6][7][8]. Furthermore, the dysfunction of B cell activation and B cell subset levels have also been suggested to be associated with the development of pAPS, but the phenotype changes of B cells and the potential mechanisms of B cell changes and autoantibody generation remain unknown [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic IL‐6 levels collected from previous studies of various IMID populations were highly varied, as show in Figure 1 , ranging from 3.6 to 30.2 pg/ml in SLE, 1.3 to 85 pg/ml in UC, 4.25 to 47 pg/ml in CD, and 2.1 to 187 pg/ml in T1D. 11 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 The calculated mean ± SD of systemic IL‐6 levels were 12.7 ± 8.5, 23.9 ± 27.6, 20.6 ± 19.8, 56.7 ± 75.6 pg/ml in SLE, UC, CD, and T1D patient populations, respectively. The reported local GI tissue IL‐6 concentration in patients with UC and CD were also highly variable: 917–5885 pg/ml for UC and 704–7649 pg/ml for CD based on patient‐derived cell culture.…”
Section: Resultsmentioning
confidence: 99%
“…Literature data of systemic baseline IL‐6 levels in healthy subjects 22 and in patients with UC, CD, SLE and T1D, 11 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 and baseline IL‐6 levels in the local GI tract of patients with UC and CD were collected and examined. 43 , 49 , 50 , 51 , 52 , 53 The systemic or local IL‐6 concentrations obtained from different studies were pooled and the average IL‐6 levels with associated variability was calculated with GraphPad (GraphPad Software, Inc.).…”
Section: Methodsmentioning
confidence: 99%